Pendampingan Pastoral terhadap Orang Muda Katolik dalam Mengembangkan Bakat Kewirausahaan di Paroki Santo Petrus Kanisius Manufui - Uskono, Yovita; Ukat, Kristophorus (JURNAL PROPHETA, 2023)
The aim of this research is to find out how to provide pastoral assistance and forms of pastoral assistance to OMK in developing their entrepreneurial talents. The type of research used is qualitative research with the measuring tools used are observation, interviews and documents. This means that researchers will describe and describe the objects of research results so that they can group and conclude problems related to OMK entrepreneurship in St. Parish. Peter Kanisius Manufui. The author also explains the reality and explores the problems faced by OMK in entrepreneurship so that they can find the right pastoral efforts in entrepreneurship. The research results show that assistance to OMK in developing entrepreneurial talent is always available. OMKs are given initial education on how to create business results and these results are used to save. Apart from that, assistance is also provided to open businesses when there are creative economy exhibitions in the Deanery and Diocese so that OMKs become more aware and courageous in creating opportunities in their home areas without having to be influenced to migrate outside the area. The form of approach taken by the parish to develop the talents and creativity of OMK is by creating spiritual activities in the parish so that OMK can see the opportunities that exist to create businesses. With this assistance, OMK began to dare to develop the talent and creativity around the